Luteolin affects keloid fibroblast proliferation and apoptosis by regulating FRAT1 gene expression - Zhang, Xueyan; Liu, Wen; Wei, Shuxiang (Cellular and Molecular Biology, 2020)
The current experiment was performed to investigate whether luteolin affects the proliferation and apoptosis of keloid fibroblasts by regulating the expression of FRAT1 gene. Keloid fibroblasts were treated with luteolin at different concentrations. MTT method, western blot, flow cytometry, and real-time quantitative PCR (qPCR) were used to detect cell proliferation, cyclin D1 (CyclinD1), p21, B-cell lymphoma / leukemia-2 (Bcl-2), Bcl-2 related X protein (Bax), FRAT1 protein expression, apoptosis and ARHI mRNA expression. Keloid fibroblasts were transfected with si-FRAT1, or pcDNA-FRAT1 and treated with luteolin to observe their roles in cell proliferation and apoptosis. Compared with the control group, luteolin significantly reduced the keloid fibroblast activity, CyclinD1, Bcl-2, and FRAT1 protein levels, and obviously improved the cell apoptosis rate, p21 and Bax protein expression (P<0.05). The expression of FRAT1 mRNA and protein in keloid fibroblasts was greatly increased (P<0.05). Inhibition of FRAT1 expression evidently decreased cell viability at 24 h, 48 h, and 72 h, CyclinD1, and Bcl-2 protein expression of keloid fibroblasts, while-dramatically enhanced cell apoptosis, p21, and Bax protein levels (P<0.05). FRAT1 overexpression reversed the inhibitory effect of luteolin on keloid fibroblast activity, FRAT1, CyclinD1, and Bcl-2 protein expression, and promotion of apoptosis, p21 and Bax protein expression. Luteolin can inhibit the proliferation and induce apoptosis of keloid fibroblasts by regulating the expression of FRAT1 gene.